Genome-Wide Identification and Expression Analysis of Terpene Synthase Genes in Cymbidium faberi - Wang, Qian-Qian; Zhu, Meng-Jia; Yu, Xia; Bi, Yuan-Yang; Zhou, Zhuang; Chen, Ming-Kun; Chen, Jiating; Zhang, Diyang; Ai, Ye; Liu, Zhong-Jian; Lan, Siren (Frontiers in Plant Science, 2021)
Terpene synthases (TPSs) are essential for forming terpenes, which play numerous functional roles in attracting pollinators, defending plants, and moderating the interaction between plants. TPSs have been reported in some orchids, but genome-wide identification of terpenes in Cymbidium faberi is still lacking. In this study, 37 putative TPS genes were classified in C. faberi and divided into five subfamilies (TPS-a, TPS-b, TPS-c, TPS-e/f, and TPS-h). Motif and gene structure analysis revealed that most CfTPS genes had the conserved aspartate-rich DDxxD motif. TPS genes in the TPS-a and TPS-b subfamilies had variations in the RRX8W motif. Most cis-elements of CfTPS genes were found in the phytohormone responsiveness category, and MYC contained most of the numbers associated with MeJA responsiveness. The Ka/Ks ratios of 15 CfTPS gene pairs were less than one, indicated that most CfTPS genes have undergone negative selection. The tissue-specific expression patterns showed that 32 genes were expressed in at least one tissue in C. faberi, and TPS genes were most highly expressed in flowers, followed by leaves and pseudobulbs. In addition, four CfTPS genes were selected for the RT-qPCR experiment. The results revealed that CfTPS12, CfTPS20, CfTPS26, and CfTPS32 were mainly expressed in the full flowering stage. These findings of CfTPS genes of C. faberi may provide valuable information for further studies on TPSs in orchids.